Human Plasmodium knowlesi infections in young children in central Vietnam - Eede, P.V.; Van, H.N.; Van Overmeir, C.; Vythilingam, I.; Duc, T.N.; Hung, L.X.; Manh, H.N.; AnnÃ©, J.; D'Alessandro, U.; Erhart, A. (2009)
Background Considering increasing reports on human infections by Plasmodium knowlesi in Southeast Asian countries, blood samples collected during two large cross-sectional malariometric surveys carried out in a forested area of central Vietnam in 2004 and 2005 were screened for this parasite. Methods Blood samples collected at the 2004 survey and positive for Plasmodium malariae were randomly selected for PCR analysis detecting P. knowlesi. Blood samples collected in 2005 from the same individuals were screened again for P. knowlesi. Positive samples were confirmed by sequencing. Family members of positive cases who participated in both surveys were also screened. Results Ninety-five samples with P. malariae mono- or mixed infections identified by species-specific PCR were screened for P. knowlesi. Among the five (5.2) positive samples by PCR, three were confirmed to be P. knowlesi infections by sequencing, two young children (<5 years old) and a young man, all asymptomatic at the time of the survey and for the next six months after the survey. One of the two children was still positive one year later. No infection was found among the family members. Conclusion Plasmodium knowlesi infections in humans can be found in central Vietnam. A small child was positive for P. knowlesi in both surveys at one year interval, though it is unclear whether it was the same or a new infection.